(untitled) (Transport systems and technologies, 2022)
In order to reduce the load of the load-bearing structure of the flat wagon during operating conditions, in particular shunting operations, the use of energy-globalizing material in its composition was suggested. This solution is implemented by creating a closed design of the backbone and the main restrained beams filled with a reinforcement with pipe-in-noise properties. Investigations were carried out with regard to the flat car model 13-401. In order to substantiate the suggested solution the mathematical modeling of dynamic load-carrying capacity of the flat wagon loaded with two tank-containers of 1CC size at shunting coupling was carried out. The mathematical model was developed by the Runge-Kutt method in the MathCad software. It was found that dynamic load of the flat car load-bearing structure with the suggested solutions reduced by 3.2% in comparison with the load-bearing structure without a surge suppressor. The strength of the load-bearing structure of the flat wagon was calculated by the method of joined elements, which was implemented in the SolidWorks Simulation program complex. The results of calculations showed that the maximum equivalent loads do not exceed the permissible values and are 14% lower than those occurring in the typical flatcar design. The conducted research will contribute to the creation of innovative designs of freight cars as well as to the increase of efficiency of rail transport utilization.